Microscopic studies on postmortem vermiform appendix of the adult males of Bangladesh. (February 2016) - Bakar, S.; Shamim, M.; Salam, A.; Sultana, S.
Abstract Background The anatomy of the vermiform appendix shows variations in its macroscopic dimensions and microscopic features, some of which have potentials of influencing the clinical aspects of the appendix. Aim The aim of this study was to find out some microscopic features of appendix and evaluate the correlation between the microscopic features of the appendix and the age of the subjects and to determine whether these findings should influence the clinical implications of appendix. Methods In this cross-sectional observational study, thirty adult males' (age from 18 to 67 years) postmortem appendices and adnexa from Bangladeshi victims of road traffic accidents were sectioned at the base, midzone and tip stained with H+E stain and examined under microscope. Measurements were taken at the base, at the midzone and at the tip of the appendix, and the mean of the three measurements was considered as the overall value. Results The overall number of mucosal glands in a section ranged from 42.33 to 130.00 and the number of the germinal centres varied between 2.33 and 10.00. The overall luminal diameter ranged between 1764.58 and 3208.33 µm. The overall luminal diameter in more than 52 % of cases was between 2700.00 and 3299.99 µm with a median value of 2750 µm. Conclusion The overall number of mucosal glands showed a tendency towards a positive correlation with age. The overall luminal diameter and the overall number of germinal centres showed a tendency towards a negative correlation with the age. However, none of the tendencies of correlation reached statistically any significant level.